2012
DOI: 10.1111/j.1742-7924.2012.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy for inpatients with chronic schizophrenia: A pilot randomized controlled trial

Abstract: Aim: People with schizophrenia tend to experience difficulties in social and cognitive function, self-care, residual negative symptoms, high rates of unemployment, and social exclusion. Occupational therapy has contributed to the treatment and rehabilitation of people with severe mental health problems. Therefore, this study investigated the effects of occupational therapy on symptoms of patients with schizophrenia. Methods: This survey was an experimental study in which positive and negative symptoms of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 25 publications
(37 reference statements)
2
33
0
5
Order By: Relevance
“…Several studies have examined the effects of OT on patients with schizophrenia. Many of these reported that OT can improve symptoms, and combined interventions of OT and pharmacological treatment can more effectively improve symptoms than pharmacological treatment alone (Foruzandeh and Parvin, ; Hoshii et al, ). However, the effectiveness of OT for cognitive impairment in patients with acute schizophrenia has not been sufficiently verified.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the effects of OT on patients with schizophrenia. Many of these reported that OT can improve symptoms, and combined interventions of OT and pharmacological treatment can more effectively improve symptoms than pharmacological treatment alone (Foruzandeh and Parvin, ; Hoshii et al, ). However, the effectiveness of OT for cognitive impairment in patients with acute schizophrenia has not been sufficiently verified.…”
Section: Introductionmentioning
confidence: 99%
“…The authors noted the need for temporal/longitudinal studies to investigate causality of the observed associations. Other authors have noted the beneficial effects of occupational therapy on psychological distress, dysfunctional symptoms and outcomes among schizophrenia patients [23], [24], and among community-dwelling adults with a mental health diagnosis [25]. It is possible that routine engagement in work during the work week may explain reduced potential PA admissions among PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Síntomas: Se encontraron dos artículos que reportaron los resultados de ensayos clínicos controlados que evaluaron la eficacia de la terapia ocupacional para disminuir los sínto-mas en pacientes con esquizofrenia crónica que tenían larga estancia de hospitalización 11,12 . El primer artículo fue realizado en Japón 11 , con pacientes que tenían más de 10 años de enfermedad y que se habían rehusado a otros tratamientos psicosociales como educación y entrenamiento en habilidades sociales.…”
Section: Terapia Ocupacionalunclassified
“…La terapia ocupacional se basa en la realización de diferentes actividades que le permiten al paciente experimentar con otros y comunicarse 11 . Esta intervención se basa en la ciencia ocupacional que postula que el estar comprometido en actividades significativas y satisfactorias contribuye a la salud en general y a la percepción de bienestar del paciente, como también a mejorar el funcionamiento y la inclusión sociales, las relaciones en el ambiente local y la autoestima 12,13 .…”
Section: Introductionunclassified